Activity Disengagement: Understanding Challenges and Opportunities for Reengagement - Krista Fox; Nancy Morrow-Howell; Stephanie Herbers; Paula Battista; Carolyn M. Baum (Occupational Therapy International)
Although maintaining engagement in activities has a positive influence on our health and wellbeing as we age, many programs that serve older adults struggle with getting participation in the programs they offer. This study sought to explore activity disengagement among older adults in a senior housing community and identify the challenges and opportunities for reengagement with the aim of informing future intervention development and testing. Fifty-one adults over the age of 60 participated in structured interviews. Findings highlighted that many older adults have activities patterns that are not optimal for health. Many reasons given for disengaging in activities (e.g., no opportunity) were surprising given that participants lived in a setting where a variety of programs were offered. Programs need to more purposively address social challenges to participating in activities and consider a more person-centered approach when developing interventions for the older adults they serve.